Women's responses to nausea and vomiting in pregnancy. - Locock, L; Alexander, J; Rozmovits, L (2008)
OBJECTIVE: To explore women's experiences of nausea and vomiting in pregnancy. DESIGN: secondary (thematic) analysis of data collected by narrative interviews for two wider studies about antenatal screening and about pregnancy for the DIPEx website (www.dipex.org). PARTICIPANTS AND SETTING: A maximum variation sample was recruited throughout the UK. Data from the 73 women interviewed have been analysed. Interviews took place between October 2003 and December 2004, mostly in the home. FINDINGS: sickness is considered a typical and almost inevitable feature of pregnancy. Against this backdrop, a new framework for understanding women's responses to nausea and vomiting in pregnancy, and the meanings they attach to it, is suggested: nausea and vomiting as something to be expected, survived, resisted, resented, and acknowledged by others. KEY CONCLUSIONS: The concepts of loss of self and biographical disruption from the field of chronic illness seem to resonate with the women's experiences, and may perhaps be extended to transient as well as chronic health conditions. People's experiences of their bodies in health as well as illness need to be more widely studied. IMPLICATIONS FOR PRACTICE: Many women would appreciate greater acknowledgement of the distress nausea and vomiting in pregnancy causes them, information about remedies and strategies other women have found helpful, and reassurance. Expressions of empathy by health-care professionals are frequently lacking and particularly desired.